Pertumbuhan Anak Itik Magelang dari Induk yang Diberi Suplementasi Kurkumin dan Dipajan Cahaya Merah (THE GROWTH OF DUCKLINGS FROM DUCKS THAT GIVEN CURCUMIN SUPPLEMENTATION AND RED LIGHT EXPOSURE) - Albab, Luthfiana Ulil; Isdadiyanto, Sri; Djaelani, Muhammad Anwar; Kasiyati, Kasiyati (Jurnal Veteriner, 2019)
This research aimed to study the effect of curcumin supplementation and red light exposure to the growth of magelang ducklings. The research design used complete randomized design that divided into four groups and each group consists of five ducklings, they were ducklings from ducks which was not given curcumin and exposed to white light (control), ducklings from ducks which was not given curcumin and exposed to red light (P1), ducklings from ducks was given curcumin 18 mg/head/day and white light (P2) and ducklings from ducks was given curcumin 18 mg/head/ day and red light (P3). The curcumin that given to the duck were mixed with feed as a supplement. The variables of this research were the body weight and morphometry that consisted of the chest perimeter, abdominal perimeter, and fur necklace (the white fur that surounded the neck) width . The collected data were analized with Kruskal Wallis non parametric test and would be further tested with Mann Whitney-U test and linear regression. The result of this research showed that curcumin supplementation and red light exposure to ducks affected the body weight, chest perimeter, abdominal perimeter, and fur necklace width of magelang ducklings. We concluded that 18 mg curcumin supplementation and red light exposure increased ducklings quality, we hope 18 mg curcumin supplementation and red light exposure can be applied to increase ducklings quality, futhermore the ducklings have better productivity.